Differentiation of mesenchymal stem cells using metal oxide thin films. (23rd March 2021) - Khokhlova, M; Hammad, M; Lhuissier, E; Retoux, R; Goux, D; Fouchet, A; David, A; Lüders, U; Boumediene, K; Prellier, W
Abstract: While metal oxides synthesized as thin films have attracted much attention due to their electronic applications, we show here that they can also be used as bio-surfaces for the growth of stem cells, a field of research which has not been much explored. To demonstrate this, thin films (150–200 Å) of titanium oxide (TiO2 ) and aluminum oxide (Al2 O3 ) were deposited on glass using the pulsed laser deposition technique and mesenchymal stem cells were grown on these layers. Cell behavior was evaluated with respect to various key parameters, such as the composition, wettability, morphology and thickness of the films. Our results indicate that thin films of TiO2 and Al2 O3 can not only support stem cell adhesion and growth, but can be used to influence the osteogenic and chondrogenic differentiation paths, which opens the route for a variety of novel biocompatible materials.